THE EFFECT OF GOVERNMENT ACCOUNTING STANDARDS AND GOVERNMENT INTERNAL CONTROL SYSTEMS ON THE QUALITY OF LOCAL GOVERNMENT FINANCIAL STATEMENTS - Endang Darmawan (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
This study aims to determine how the influence of the adoption of government accounting standards and internal control systems of the government on the quality of local government financial reports on the SKPD in Bandung. The research method used in this study is the explanatory method. The results showed that partially and simultaneously the application of government accounting standards and the government's internal control system affected the quality of local government financial reports.